CULTURAL VALUES REFLECTED IN ENGLISH AND UZBEK PROVERBS: A COMPARATIVE STUDY - B.Tog’ayev; S.Sattorova (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article examines the cultural values reflected in English and Uzbek proverbs from a comparative point of view. The topic is important because proverbs are not only short fixed expressions. They also preserve social memory, moral advice, and national ways of thinking. The article analyzes how common values such as work, honesty, patience, friendship, family, and mutual help are expressed in the two proverb traditions. Attention is also given to differences in worldview. English proverbs often sound brief, practical, and individual-centered, while Uzbek proverbs more often stress family ties, collective life, respect, and hospitality. The study uses comparative, descriptive, and contextual methods. Proverbs are grouped by theme, compared in meaning and form, and then discussed as cultural signs. The discussion section includes selected proverb extracts with short analysis and footnote support. The results show that many values are shared by both cultures, but the way they are presented depends on each person’s social experience and national mentality. The article concludes that proverbs are a useful source for studying language and culture together, and they can also support comparative linguistics, translation studies, and foreign language teaching.